The design and analysis of low-cost myoelectric hand using six-bar linkage mechanism - Ismail, Rifky; Ariyanto, Mochammad; Wicaksono, Luthfi R.; Ispramuditya, Aditya; Putri, Farika T. (Asia-Pacific Journal of Science and Technology, 2021)
This study discussed the development of an affordable myoelectric prosthetic hand using a six-bar linkage. This involved the design of the index, middle, ring, and little finger using computer-aided design software with the application of two six-bar linkages as the main mechanism. The fingertip trajectories were also simulated using the software before the hand prototype was built after which they were analyzed based on six-bar linkage using the trigonometric law. Moreover, the hand design was developed using 3D printing technology while six grip patterns were implemented to ensure the hand performs the required daily activities, and individual grip force for each finger was measured using a calibrated force-sensitive resistor. The experimental results showed the designed six grip patterns successfully pick and grasp several objects with different weights, shapes, and sizes. The proposed BimoHand has individual grip force at the fingertip ranging from 0.5886 N to 1.373 N and also successfully gripped and handle a fragile object such as an egg by adjusting the human hand flexion and extension without breaking it. It has a total mass of 251 grams excluding socket hand and batteries and this lightweight makes it comfortable and easy to use in daily activities. The hand is relatively affordable and lighter compared to other available myoelectric hands.